Kajian Literatur: Massage untuk Peningkatan Kualitas Tidur pada Pasien Kritis - Sari, Nindya Rachma Gardhika; Utami, Reni Sulung (Holistic Nursing and Health Science, 2022)
Introduction: Sleep disturbance is one of the complaints in criticaly illl patients and have an impact on the patient's physical and psychological condition. Research on the effect of massage therapy on sleep quality has been widely studied with various techniques and outcomes. This study aims to review the evidence regarding the location, equipment, dose and timing of massage that can improve sleep quality in critically ill patients.Methods: This research method is a literature review. Literature is searched through electronic database such as EBSCOhost, Scopus, Science Direct, ProQuest, Clinical Key, SpringerLink and Portal Garuda. The keywords used are massage, massages, reflexology,”pemijatan”, “pijat”, sleep, sleep disturbance, sleep deprivation, sleep apnea, sleep quality, quality of sleep, critical area, critical patients, intensive care unit, and ICU. The inclusion criteria of article was  an experimental research design that tested the effect of massage on improving sleep quality, full text articles and published from January 2011 to May 2021. Data were analyzed in a narrative manner and grouped according to the searched theme, namely location/area, equipment, dose and timing of massage.Results: Search results found 107 articles, but only 9 articles were eligible to be reviewed. The review indicate that massage has a significant effect on improving sleep quality. The combination of hand and valerian or lavender essential oil is the most appropriate way. Feet are the most numerous and effective area. Massage dose is once a day with repetitions for two consecutive days with a duration of 10-20 minutes and it carried out before bedtime.Suggestion: This result recommend the application of massage to improve the sleep quality of critically ill patients. However, massages which given to critically ill patients must be carried out by certified nurses or expert in massage.